Processing math: 0%

Pages

modulo - Part 1


Today we will look at an important concept in number theory -- the concept of modulo. Two integer numbers a and b are said to be equal modulo n iff they have the same remainder when divided by n. Or equivalently, iff (a-b) is divisible by n. We will write a = b \pmod{n}.


For example, 5 = 9 \pmod{2}, -1 = 3 \pmod{2}, -2 = -8 \pmod{2}. Based on modulo 2 then  for any number a, either a=0 \pmod{2} when it is an even number, or a=1 \pmod{2} when it is an odd number. 
Here are a few other examples:
0 = 3 = 6 = 9 = 12 = -3 = -6 \pmod{3},
1 = 4 = 7 = -2 = -5 \pmod{3},
2 = 5 = 8 = -1 = -4 \pmod{3},
0 = 4 = 8 = -4 \pmod{4},
1 = 5 = -3 = -7 \pmod{4},
2 = 6 = -2 = - 6 \pmod{4},
-2 = -14 \pmod{6}, ~~~7 = -14 \pmod{7}, ~~~5 = -3 \pmod{8}, ~~~16 = -2 \pmod{9}, ...

Recall the definition, we define that a = b \pmod{n} when a-b is divisible by n and read "a is equal to b modulo n".

Let us look at some of the properties of modulo.

Addition Rule:
If a = b \pmod{n} and x = y \pmod{n} then a +x = b + y \pmod{n}.

This is similar to our usual addition rule, that is when a = b and x=y then a+x = b+y. Here, we just simply add modulo n to the end of the formula. For example, from 13 = 1 \pmod{4} and 2 = 6 \pmod{4} we have 15 = 7 \pmod{4}.

To prove this Addition Rule, we just need to use the definition. Since a = b \pmod{n}, a-b is divisible by n. Again, since x = y \pmod{n}, x-y is divisible by n. Sum of two multiples of n is a multiple of n, so (a-b)+(x-y) is divisible by n. We have (a-b)+(x-y) = (a+x) - (b+y), so because (a+x) - (b+y) is divisible by n, by the definition, we have a +x = b + y \pmod{n}.  So the Addition Rule is proved. Let us look at other properties.


Addition Rule (special case): 
If a = b \pmod{n} then a + z = b + z \pmod{n}.

This special case is derived from the main Addition Rule. We apply a = b \pmod{n} and z = z \pmod{n} and get a + z = b + z \pmod{n}.


Subtraction Rule:
If a = b \pmod{n} and x = y \pmod{n} then a - x = b - y \pmod{n}.


Subtraction Rule (special case): 
If a = b \pmod{n} then a - z = b - z \pmod{n}.


Multiplication Rule:
If a = b \pmod{n} and x = y \pmod{n} then a x = b y \pmod{n}.


Multiplication Rule (special case): 
If a = b \pmod{n} then a z = b z \pmod{n}.


Exponentiation Rule:
If a = b \pmod{n}  then a^k = b^k \pmod{n}.


The Exponentiation Rule is derived from the Multiplication Rule. We apply a = b \pmod{n} and a = b \pmod{n} and get a^2 = b^2 \pmod{n} from the Multiplication Rule. Again using the Multiplication Rule for a^2 = b^2 \pmod{n} and a = b \pmod{n}, we get a^3 = b^3 \pmod{n}.  So by repeating this process, we get a^k = b^k \pmod{n} for all values of k.

Homework: Prove the Subtraction Rule and the Multiplication Rule.

We will meet again in "modulo - Part 2" when we talk about some applications of modulo.